2023
DOI: 10.1002/msc.1832
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatology nurses' perceptions of undertaking a postgraduate education programme: A phenomenological study

Sarah Ryan,
Andrew Hassell,
Zoe Paskins
et al.

Abstract: BackgroundThe expansion of the role of the rheumatology nurse specialist led to the instigation, in 1999, of the first Masters programme in rheumatology nursing, with the aim of supporting clinical advancement with evidence‐based practice. This study explored the experience of rheumatology nurses undertaking postgraduate study at Masters level.Objectives(1) To explore the perceptions and experiences of clinical nurse specialists undertaking a Masters programme in Rheumatology Nursing, including perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In some countries, postgraduate education is planned so that rheumatology nurses can take a more active role in the follow-up and treatment of patients. Ryan et al [ 59 ], in their study with nurses who received postgraduate education in rheumatology, reported that receiving postgraduate education increased self-confidence and new clinical and critical evaluation skills. Obtaining postgraduate education in rheumatology poses several challenges.…”
Section: Health Promotion and Nurses In Rheumatic And Musculoskeletal...mentioning
confidence: 99%
“…In some countries, postgraduate education is planned so that rheumatology nurses can take a more active role in the follow-up and treatment of patients. Ryan et al [ 59 ], in their study with nurses who received postgraduate education in rheumatology, reported that receiving postgraduate education increased self-confidence and new clinical and critical evaluation skills. Obtaining postgraduate education in rheumatology poses several challenges.…”
Section: Health Promotion and Nurses In Rheumatic And Musculoskeletal...mentioning
confidence: 99%